Mainstreaming inclusive education in madrasah ibtidaiyah: A study of policy, curriculum, and teachers’ roles - Saihan Saihan; Abdul Karim; Anjum Younas Raja (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2026)
Inclusive education in Madrasah Ibtidaiyah faces three main challenges: informal policies without written regulations, improvised curricula without standardized guidelines, and dependence on teachers as compensatory actors. This study aims to analyze inclusive education practices in Madrasah Ibtidaiyah, focusing on madrasah policies, the implementation of inclusive curricula, and teachers’ roles in supporting children with special needs. This research employed a qualitative case study at Private Islamic Primary School 30 Bustanul Ulum Ambulu. Data were collected through interviews, observations, documentation, and focus group discussions, and were analyzed using inductive thematic analysis with source-method triangulation to ensure the credibility of the findings. The study found that: 1) madrasah inclusive policies are based on empathy and social justice but remain institutionally unembedded, limiting services to children with mild special needs; 2) the inclusive curriculum is implemented informally through modification, differentiation, dual learning, and individualized assistance, depending on teachers’ pedagogical creativity in the classroom; and 3) teachers act as the main agents of inclusion through adaptation, assistance, motivation, emotional support, and family coordination, exceeding the support provided by the madrasah’s formal institutional system. This study concludes that inclusion in madrasah exists as an empathy-based socio-pedagogical practice but has not yet been institutionalized, making it dependent on teachers’ commitment and limited to children with mild special needs. This study recommends that madrasahs institutionalize inclusive education through written regulations, adaptive curricula, teacher training, accessible facilities, special assistant teachers, and family collaboration to ensure sustainable, measurable, and systemic services for children with special needs.